Effect of Yield Silver Nanoparticles in Enhancing Raman Signal of SERS Substrate Fabricated on Whatman Filter Paper - Affi Nur Hidayah; Yuliati Herbani; Djoko Triyono; Rosari Saleh (Journal of Physics and Its Applications, 2022)
On Whatman Filter Paper, Surface Enhanced Raman Scattering (SERS) Substrate was created from colloidal silver nanoparticles by drop casting in varied volume colloidal nanoparticles of 3 ml and 6 ml. Using Raman Spectroscopy, SERS substrates were investigated for their ability to enhance 500 ppm of Deltamethrin pesticides Raman Signal. The number of colloidal nanoparticles is related to the volume of colloidal nanoparticles, indicating that high yields nanoparticle synthesis. The results demonstrate that fabricating SERS substrates in 6 ml increased Raman signal more than fabricating nanoparticles in 3 ml.